Intestinal stenosis of Garré: A rare cause of small bowel obstruction in the virgin abdomen. (2016) - Ismael, Hishaam; Ragoza, Yuri; Cox, Steven
Highlights: Reports of strictures following strangulated hernia repair are few, presented in different languages, and the data is frequently incomplete. We present a case report and a comprehensive literature review over the last century. Intestinal stenosis of Garré was more frequently reported to follow inguinal hernia repair than femoral hernia repair (57.1% vs. 42.9%). Most males developed a delayed stricture following an inguinal hernia repair (93.3%). 84.6% of females, on the other hand, developed intestinal stenosis following repair of a femoral hernia 87.5% of strictures developed on the right side. The terminal ileum is the narrowest part of the small bowel and is the segment where a stricture would result in the biggest impact. The timing of development of a bowel obstruction is very variable and ranges from 5 days to 22 years. 22 patients (68.8%), however, presented with an obstruction within 5 months of hernia repair. Abstract: Introduction: Small bowel obstruction (SBO) in the virgin abdomen usually requires operative intervention. Intestinal stenosis of Garré is a rare and frequently missed cause of SBO following hernia repair. Methods: We describe a case of intestinal stenosis of Garré and provide a comprehensive review of the literature. Statistical analysis was performed using IBM SPSS Statistics V.22 software and included descriptive analysis. Results: Most males developed a delayed stricture following an inguinal hernia repair (93.3%). 84.6% of females, on the other hand, developed intestinal stenosis following repair of a femoral hernia. 87.5% of strictures developed on the right side. The timing of development of a bowel obstruction is very variable and ranges from 5 days to 22 years. 22 patients (68.8%), however, presented with an obstruction within 5 months of hernia repair. Conclusions: Intestinal stenosis of Garré is an under-reported cause of delayed stricture formation.It is most common following right inguinal hernia repair in men and right femoral hernia repair in women.